Upgrading analytical models to predict the onset of degradation in selective laser sintering - Ruben Vande Ryse; Mariya Edeleva; Aico Patoor; Frederik Pille; Dagmar R. D’hooge; Ludwig Cardon (Virtual and Physical Prototyping, 2024)
ABSTRACTThe optimisation of selective laser sintering (SLS) of polymeric materials, based on analytical equations providing fast predictions, can broaden the SLS application area. However, the selection of SLS polymeric materials is currently rather limited, due to specific requirements regarding sufficient flowability and limited molecular degradation. The present work highlights that upgrading existing analytical equations, by incorporating a well-calculated overlay factor and correcting for pre-heating starting at ambient conditions, can accelerate SLS screening. Model validation is performed based on density, colorimetric, morphological and mechanical analysis of printed parts, focusing on the prediction of the laser power which corresponds to the onset of degradation, taking polyamide powder as a reference case. Furthermore, the optimised model is successfully applied for two other polymer powders, namely thermoplastic co-polyester and thermoplastic polyurethane powder, to highlight a better overall description of the SLS degradation mechanism.